Grid-cell modules remain coordinated when neural activity is dissociated from external sensory cues - Waaga, Torgeir; Agmon, Haggai; Normand, Valentin A; Nagelhus, Anne; Gardner, Richard J; Moser, May-Britt; Moser, Edvard I; Burak, Yoram (Neuron (Cambridge, Mass.), 2022)
The representation of an animal's position in the medial entorhinal cortex (MEC) is distributed across several modules of grid cells, each characterized by a distinct spatial scale. The population activity within each module is tightly coordinated and preserved across environments and behavioral states. Little is known, however, about the coordination of activity patterns across modules. We analyzed the joint activity patterns of hundreds of grid cells simultaneously recorded in animals that were foraging either in the light, when sensory cues could stabilize the representation, or in darkness, when such stabilization was disrupted. We found that the states of different modules are tightly coordinated, even in darkness, when the internal representation of position within the MEC deviates substantially from the true position of the animal. These findings suggest that internal brain mechanisms dynamically coordinate the representation of position in different modules, ensuring that they jointly encode a coherent and smooth trajectory.